2021
DOI: 10.7717/peerj.11780
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification and analysis of the YABBY gene family in Moso Bamboo (Phyllostachys edulis (Carrière) J. Houz)

Abstract: Background The YABBY gene family is a family of small zinc finger transcription factors associated with plant morphogenesis, growth, and development. In particular, it is closely related to the development of polarity in the lateral organs of plants. Despite being studied extensively in many plant species, there is little information on genome-wide characterization of this gene family in Moso bamboo. Methods In the present study, we identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 101 publications
1
9
0
Order By: Relevance
“…We identified 9 candidate genes within an interval of 50 kb up- and downstream of the SNP variant. Among those genes, it is noteworthy to mention the PH02Gene21516.t2 ( Ma et al, 2021 ) that encodes a plant-specific YABBY transcription factor (TF) ( Supplementary Table 7 ). These small zinc finger TFs are associated with plant morphogenesis, the development and polarity of lateral plant organs ( Bowman, 2000 ; Kumaran et al, 2002 ), and biotic/abiotic stress ( Yamada et al, 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“…We identified 9 candidate genes within an interval of 50 kb up- and downstream of the SNP variant. Among those genes, it is noteworthy to mention the PH02Gene21516.t2 ( Ma et al, 2021 ) that encodes a plant-specific YABBY transcription factor (TF) ( Supplementary Table 7 ). These small zinc finger TFs are associated with plant morphogenesis, the development and polarity of lateral plant organs ( Bowman, 2000 ; Kumaran et al, 2002 ), and biotic/abiotic stress ( Yamada et al, 2011 ).…”
Section: Resultsmentioning
confidence: 99%
“… 29 Except for PgYABBY2 , which had only a few conserved amino acids, all P. grandiflorus YABBY proteins featured YABBY and zinc finger domains. 36 Two highly conserved motifs were found in the YABBY proteins, which were speculated to be related to the conserved domains of the YABBY transcription factor and the YABBY and zinc finger domains. PgYABBY2 contained only one conserved motif, rendering it different from other PgYABBY proteins, but the reason for this difference remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, 20 YABBY TFs were identified in wheat. There are more YABBY members in wheat than in rice ( Toriba et al, 2007 ), Arabidopsis ( Siegfried et al, 1999 ), soybean ( Zhao et al, 2017 ), tomato ( Huang et al, 2013 ), and Moso Bamboo ( Ma et al, 2021 ), indicating that wheat YABBY has a more complex function. This reason is because wheat is a heterozygous polyploid.…”
Section: Discussionmentioning
confidence: 99%
“…To date, identification of YABBY TFs has been performed in different plant species through genome-wide analyses. A total of six YABBY TFs have been identified in Arabidopsis ( Siegfried et al, 1999 ), 17 in soybean ( Glycine max ) ( Zhao et al, 2017 ), 9 in pineapple (Ananas comosus) ( Li & Li, 2019 ), seven in grapevine ( Vitis vinifera ) ( Zhang et al, 2019 ), nine in tomato (Solanum lycopersicum) ( Huang et al, 2013 ), 12 in Gossypium arboreum , 12 in G. raimondii , 23 in G. hirsutum ( Yang et al, 2018 ), and 16 in moso bamboo ( Phyllostachys edulis) ( Ma et al, 2021 ). As one of the most important crops worldwide, the genome of wheat has been sequenced; however, few studies have been conducted on the wheat YABBY gene family.…”
Section: Introductionmentioning
confidence: 99%